Editor's Choice – Metformin Prescription is Associated with a Reduction in the Combined Incidence of Surgical Repair and Rupture Related Mortality in Patients with Abdominal Aortic Aneurysm. (January 2019) - Golledge, Jonathan; Morris, Dylan R.; Pinchbeck, Jenna; Rowbotham, Sophie; Jenkins, Jason; Bourke, Michael; Bourke, Bernard; Norman, Paul E.; Jones, Rhonda; Moxon, Joseph V.
Abstract : Objectives: Currently there is no drug therapy for abdominal aortic aneurysm (AAA) and most previous investigations have focused on imaging rather than clinical outcomes. The aim of this study was to assess whether AAA related clinical events were lower in patients prescribed metformin. Methods: This was a prospective cohort observational study performed in three cities in Australia, which was designed to study risk factors for clinical events not simply to focus on metformin. Patients with an asymptomatic unrepaired AAA of any diameter ≥30 mm were recruited from hospital outpatient clinics and surveillance programs run at four centres. The main outcome was the requirement for AAA repair or AAA related mortality (AAA events). The association between metformin prescription and AAA events was assessed using Kaplan–Meier analysis and Cox proportional hazard analysis. Results: Patients (1, 080) with a mean (SD) initial AAA diameter of 46.1 (11.3) mm were followed for a mean (SD) of 2.5 (3.1) years until an AAA event ( n  = 454), death ( n  = 176), loss to follow up ( n  = 128), or completion of current follow up ( n  = 322). Patients with diabetes who were prescribed metformin (adjusted HR 0.63, 95% CI 0.44–0.93), but not patients with diabetes who were not prescribed metformin (adjusted HR 1.15, 95% CI 0.83–1.59), had a lower incidence of AAA events compared with those without diabetes. Findings were similar in sensitivity analyses restricted to patients with an initial AAA diameter ≤50 mm and patients with a minimum follow up of six months before an AAA event. Conclusions: These findings suggest that clinically important AAA events may be reduced in patients with diabetes who are prescribed metformin, but not those with diabetes receiving other treatments. A randomised controlled trial is needed to definitively test whether metformin reduces AAA related clinical events in patients with small AAAs who do not have diabetes.